2014
DOI: 10.1021/am502278b
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated Silk Fibroin Films with Controllable Nanostructure Size and Secondary Structure for Drug Delivery

Abstract: The ability of drug release from SF materials was governed largely by their secondary structure. It is known that the breakage degree of the peptide chain during the silk fibroin (SF) dissolution can affect the structure, property, and applications of SF materials. To deeply understand this effect, we designed a reaction system based on CaCl2/H2O/C2H5OH ternary solvent with different ethanol content to obtain the regenerated SF films with different morphologies and secondary structures. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 50 publications
0
52
0
Order By: Relevance
“…Jiang et al developed an ultrathin SF film (45 ± 5 nm) fabricated by the layer-by-layer assembly technique; the resulting film displayed high elastic modulus and ultimate tensile strength due to its gradual self-reinforcing structure [54]. The stability of SF films used as biomaterial is significant; this property can be improved by stretching [55], water annealing [56], slow-drying [57], and alcohol immersion [58]. Methanol or ethanol are most often used to prepare water-insoluble SF films with increased β-sheet content.…”
Section: Structure Design Of Silk Fibroin-based Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al developed an ultrathin SF film (45 ± 5 nm) fabricated by the layer-by-layer assembly technique; the resulting film displayed high elastic modulus and ultimate tensile strength due to its gradual self-reinforcing structure [54]. The stability of SF films used as biomaterial is significant; this property can be improved by stretching [55], water annealing [56], slow-drying [57], and alcohol immersion [58]. Methanol or ethanol are most often used to prepare water-insoluble SF films with increased β-sheet content.…”
Section: Structure Design Of Silk Fibroin-based Biomaterialsmentioning
confidence: 99%
“…It was found that the structure and properties of SF films affected the release rate of drug delivery. SF films exhibited a slower doxorubicin release with smaller nanostructure and more β-sheet structure content [58]. Ceftazidime (CTZ) was successfully encapsulated into SF/gelatin mats and showed antibacterial effects during a release process of over six hours [71].…”
Section: Structure Design Of Silk Fibroin-based Biomaterialsmentioning
confidence: 99%
“…Until now, regenerated silk fibroin (RSF) has been widely used to fabricate RSF‐based biomaterials for tissue engineering, drug delivery, and etc. The study of RSF self‐assembly mechanism could be useful for understanding the nanoscale structure formation of RSF‐based biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Another type of fi broin-based nanomaterial reported were fi lms with controllable nanostructure (made of nanoglobules) and secondary structure, adequate as drug delivery systems. They proved successful in the sustained delivery, after an initial burst, of doxorubicin (chemotherapy drug) [ 52 ]. Electrospun silk fi broin nanofi bers were used by another research group to make nanoscaffolds (Chap.…”
Section: Silk Proteins In Nanostructuresmentioning
confidence: 99%